TO OBSERVE THE LOCALISATION OF PLACENTA IN RELATION TO PREVIOUS CESAREAN SECTION AND IT’S FETO-MATERNAL OUTCOME - Dr. Radhika Parmar, Dr. Deepa Kirar, Dr. K Padma Sandeepthi, Dr.Yashika Jain (Chelonian Research Foundation, 2024)
Objective: To observe the localization of placenta in relation to previous cesarean section and its feto-maternal outcome Materials and method: A cross sectional study was conducted among 246 Eligible participants (participants with previous LSCS and current pregnancy ≥ 20 weeks) Detailed history including menstrual history, obstetrics history, past history, personal history, marital history, family history of the patient was taken. General and obstetrical examination were carried out. All women were undergone to transvaginal or transabdominal ultrasound. Determining the placental location or any abnormal placentation with the transabdominal obstetric scan done between 28 weeks period of gestation and 42 weeks period of gestation, reassessed after 36 weeks or when patient presents in labor or with bleeding per vagina. The patients are followed up to delivery and the maternal and fetal outcomes are noted. RESULTS The mean age of the study participants was 28.69 years among which 90.7% of the cases were booked History of previous one LSCS was reported among 71.1% of the women while 28.9% were having two LSCS. Placenta previa was observed among 14.2% of the women who had previous history of LSCS. Fundo-posterior and fundo-anterior placenta was seen among 37.8% and 14.6% of the women respectively. Fundo-lateral and low-lying placenta were seen among 24% and 9.3% of the women respectively. Placenta previa and accreta are the major factors for post-partum hemorrhage Proportion of preterm birth was 10.1% Proportions of meconium-stained liquor and poor APGAR score (<7) were observed among 4.5% each of the study participants. Placenta previa was identified in 14.2% of women with a history of LSCS. To reduce the occurrence of placenta previa, it is important to reduce the number of primary cesarean procedures and promote vaginal births. For optimal care, if a patient must have c-section, routine prenatal examinations and identification of high-risk groups should be performed. Keywords: Cesarean section, Placenta previa, Maternal outcome, Fetal outcome.